The Sovereign State and Fundamental Rights Interface - Gautam, Dilli Raj (Interdisciplinary Issues in Education, 2023)
This article investigates the interface between the sovereign state and fundamental rights with the views of The Social Contract Theory. concept of the sovereign state emerged in response to specific social and economic circumstances of the time. The idea of fundamental rights i s a comparatively new phenomenon in the history of political thinking, and today’s constitutions adopt a bill of rights that outlines the legal rights of individuals, which have been prevailing within society for a long time. The Social Contract Theory is a political and philosophical foundation for the modern sovereign state, encompassing major elements of natural rights: life, liberty, and property. This study critically evaluates the topic, applying a theory-driven method and arguing that political power originates from the people, not from the grace of God. Finally, the study provides recommendations on how independent and democratic nations can put these principles into practice.